Investigating the Impact of Robotics and Automation on Manufacturing Technology - Shashank Gupta (International Journal of Manufacturing and Production Engineering, 2023)
Automation and automated machines have dramatically enhanced quality, productivity, and efficiency in industries such as manufacturing at the past few decades. The current research looks at the ways robotics and automation are impacting industrial technologies. The investigation offers an in-depth analysis of the advantages and difficulties connected with the incorporation of robots and automation in industrial processes by evaluating pertinent literature, case studies, and statistics. Conclusions of this research effort prove the fundamental nature of these developments and their potential for further developments. The overview includes definitions, evolution over time, important elements, and various kinds of robotic systems for the manufacturing process. Studying the benefits of integrating automated equipment in manufacturing, higher productivity, better quality, improved safety for employees, and cost savings are highlighted. The report also looks at forthcoming advances and their possible effects, that include Industry 4.0, AI, IoT integration, and collaborative robotics. The significance of workforce adaptability and cooperation between humans and robots is emphasized. Overall, this study shows how automation and robots have the power to revolutionise the fabrication sector by boosting profitability, ability to adapt, and competitiveness.
Keywords: collaborative robots; fabrication; industrial robots; robots; sensors